The chemistry and technology of petroleum - Speight, James G. (Chemical industries ;, 2007)
Refineries must not only adapt to evolving environmental regulations for cleaner product specifications and processing, but also find ways to meet the increasing demand for petroleum products, particularly for liquid fuels and petrochemical feedstocks. The Chemistry and Technology of Petroleum, Fourth Edition offers a 21st century perspective on the development of petroleum refining technologies. Like its bestselling predecessors, this volume traces the science of petroleum from its subterranean formation to the physicochemical properties and the production of numerous products and pe.